Places of memory of the dictatorship: disputes between the public power and social movements (Cadernos de Sociomuseologia, 2018)
The sites of memory, in Pierre Nora's perspective (1993), are spaces of eternalization of a memory's group that can no longer be spontaneously evoked by collective memory. There is a large dispute between the State and the social movements regarding the preservation of historical heritage that alludes to the Brazilian military-business coup (1964-1985) in Rio de Janeiro. We intend to think the political place of these sites of memories, consulting the patrimony of spaces and buildings which advocate for the coup and dictatorship, in the city of Rio de Janeiro. The policy that has been practiced so far by the State can be defined as conciliatory. However, the social movements demand the insertion of their voices in these places, considering them, silenced or forgotten. We are interested in analyzing these disputes and how they reflect on society.Key words: Brazilian military-business dictatorship; memory; patrimony.